2006
DOI: 10.1097/01.phm.0000214320.99729.f3
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in FIM??? Scores and Length of Stay for Underinsured Patients Undergoing Stroke Inpatient Rehabilitation

Abstract: Differences in functional independence at admission to poststroke rehabilitation and the average daily improvement in function are related, in part, to patients' race/ethnicity. Differences in change in functional independence from admission to discharge (FIM gain) are not related to race/ethnicity once other factors, particularly admission FIM score, are taken into account. Future studies should identify reasons why Hispanics have lower admission FIM scores because demographic and stroke-related variables wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 11 publications
0
30
1
Order By: Relevance
“…26 The patient sociodemographic and clinical variables were selected on the basis of the literature, preliminary screen, and clinical expertise. A review of the literature revealed the following variables that could assist in predicting disposition: the FIM, particularly the motor FIM [27][28][29][30][31] ; stroke severity, most often measured by the National Institutes of Health Stroke Scale 32-34 ; racial background [22][23][24]35 ; age at stroke onset 17,36 ; marital status 30 ; and insurance. 37 The team of clinicians and researchers further evaluated the data available for variable selection.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The patient sociodemographic and clinical variables were selected on the basis of the literature, preliminary screen, and clinical expertise. A review of the literature revealed the following variables that could assist in predicting disposition: the FIM, particularly the motor FIM [27][28][29][30][31] ; stroke severity, most often measured by the National Institutes of Health Stroke Scale 32-34 ; racial background [22][23][24]35 ; age at stroke onset 17,36 ; marital status 30 ; and insurance. 37 The team of clinicians and researchers further evaluated the data available for variable selection.…”
Section: Data Collectionmentioning
confidence: 99%
“…12,17,18 There is little information on which specific patient characteristics can be used to predict a home versus institution disposition from inpatient rehabilitation. [19][20][21][22][23][24] The purpose of this study was to examine sociodemographic and clinical characteristics independently associated with discharge home compared with discharge to a skilled nursing facility (SNF) after acute inpatient rehabilitation.…”
mentioning
confidence: 99%
“…This finding was consistent among black or African American and white patients, but only 10.6% of black or African American patients had a neurologist as their attending physician compared with 20.3% of white patients. 152 Thus, this study indicates a discrepancy in delivery of care with possible direct consequences on treatment and patient outcome.…”
Section: Differential Referral To Neurologistsmentioning
confidence: 99%
“…A retrospective cohort study found no racial-ethnic differences in admission FIM scores, 151 whereas others found significant differences in FIM scores. One study of a large urban county hospital reported that Hispanics had lower admission FIM scores than blacks or African Americans, 152 and another study found that unadjusted FIM scores were highest for whites compared with other racial groups. 153 A few studies reported no racial-ethnic differences in length of stay for inpatient rehabilitation [151][152][153] ; however, 1 study of Veterans Affairs (VA) and non-VA inpatient rehabilitation facilities reported significantly longer average lengths of stay for blacks or African Americans than for whites.…”
Section: Disparities In Access To Stroke Rehabilitationmentioning
confidence: 99%
“…In direct contrast, Berges et al noted significant differences at 3 months post injury while finding no significant differences at discharge [7]. When examining change over time, another study observed that whites demonstrated greater overall gains in FIM total and cognitive scores from admission to discharge [8], although once admission FIM scores were statistically accounted for, these significant racial/ethnic differences in post-acute rehabilitation outcomes were eliminated [9][10][11][12].…”
Section: Differences In Rehabilitation Outcomementioning
confidence: 76%